2008
DOI: 10.1177/1553350608322700
|View full text |Cite
|
Sign up to set email alerts
|

Single Port Laparoscopic Cholecystectomy With the TriPort System: A Case Report

Abstract: Single port access surgery may be the next generation of minimally invasive surgery. This study reports a recent experience with the TriPort system (trademark pending, Advanced Surgical Concepts, Wicklow, Ireland) to perform a laparoscopic cholecystectomy via a single peri-umbilical incision. To the authors' knowledge, this is one of the first cases of single port laparoscopic cholecystectomy ever performed with this device in the United States. Randomized studies to compare single port laparoscopic cholecyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
105
0
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(113 citation statements)
references
References 5 publications
1
105
0
7
Order By: Relevance
“…The adjustable double layer transparent plastic sheath is adjusted to the thickenss of the abdominal wall (up to 10 cm). [13][14][15] Comparing the ports, we found that the Triport™ was easier to insert in a 2 cm incision and is versatile on different abdominal wall thickness. The drawback is its more propensity for gas leak around the incision site, the difficulty in inserting instruments through the gelport cap and the friction encountered with instrument movement in and out of the port.…”
Section: Discussionmentioning
confidence: 95%
“…The adjustable double layer transparent plastic sheath is adjusted to the thickenss of the abdominal wall (up to 10 cm). [13][14][15] Comparing the ports, we found that the Triport™ was easier to insert in a 2 cm incision and is versatile on different abdominal wall thickness. The drawback is its more propensity for gas leak around the incision site, the difficulty in inserting instruments through the gelport cap and the friction encountered with instrument movement in and out of the port.…”
Section: Discussionmentioning
confidence: 95%
“…In recent years, after scarless endoscopic thyroidectomy was widely performed in many medical centers, the concept of a minimally invasive esthetic operation had been accepted by many surgeons, because it was welcomed by many patients (Snissarenko et al, 2009). More surgeons found that TSPLC was not as difficult as before with the development of laparoscopic technology and instrument upgrades (Romanelli et al, 2008;. Today, natural orifice transluminal endoscopic cholecystectomy, such as endoscopic cholecystectomy through gastric and vaginal access, has been successfully performed in some hospitals (Pearl and Ponsky, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Three methods could be adopted to solve the problem: (1) Hanging the cholecystic bottom to the right subcostal abdominal wall by one to three percutaneous sutures could provide adequate working room and the assistant trocar can be moved from the transumbilical incision (Philipp et al, 2009); (2) Using a Triport trocar or self-made apparatus, such as sterile gloves (Romanelli et al, 2008); (3) Using articulating instruments (Podolsky et al, 2009), such as flexible-tip laparoscope (Elazary et al, 2009) and articulating grasper. This reduces operative difficulty, but increases operation fees.…”
Section: Discussionmentioning
confidence: 99%
“…In order to perform this type of surgery, surgeons use end articulating instruments and specialized ports. The most popular commercial ports are the TriPort™ (Olympus) and SILS port™ (Covidien) [12,13]. While the benefits of single-site surgery include cosmesis and are thought to reduce postoperative pain, concerns about the complications and technical aspect of this type of surgery remain a topic of controversy.…”
Section: Introductionmentioning
confidence: 99%